LED SOURCE OF LIGHT WITH HIGH LIGHT CIRCUIT - A. N. Borisov; R. R. Shiriev (Известия высших учебных заведений: Проблемы энергетики)
Abstract: The original design of a light device with an led source of optical radiation, the light- emitting element of which is made in the form of a half-ellipsoid, is presented, which allows to minimize passive losses of crystal radiation and increase the efficiency of the radiator. The lamp can be used as a point light source in optical and electronic equipment, as a lighting device, night lamp and other types of lighting devices.